Effect of green tea on the cardiovascular system - Maternia, Jakub; Miszczyk, Karolina; Maj, Patrycja; Sergiel, Natalia; Kania, Agata; Gonet, Malwina; Włodarczyk-Cybulska, Karolina; Mozer, Piotr; Lazar, Michał; Serwik-Trandasir, Aleksandra (Journal of Education, Health and Sport, 2023)
Cardiovascular diseases (CVD) are among the leading causes of mortality worldwide, causing significant public health concerns. Flavonoids, abundant in green tea, have been found to play a pivotal role in their prevention and treatment. These compounds exert beneficial effects on vascular endothelium through various mechanisms, including enhancing nitric oxide production, reducing LDL cholesterol levels, and inhibiting platelet aggregation. Dietary principles tailored to individual risk factors are also vital for individuals with CVD. Studies suggest that green tea may be a promising tool for preventing CVD due to its antioxidative, anti-inflammatory, anti-carcinogenic, and antiplatelet effects. Catechins in green tea have been demonstrated to modify various risk factors, thereby reducing overall CVD risk. Epidemiological studies have reported an inverse association between green tea consumption and mortality from CVD. The beneficial properties of green tea, especially among non-smokers and rural residents, underscore its potential role in managing CVD risk. Further research on the effect of green tea on vascular health is warranted.